2023
DOI: 10.3390/cancers15020549
|View full text |Cite
|
Sign up to set email alerts
|

DNA and RNA Alterations Associated with Colorectal Peritoneal Metastases: A Systematic Review

Abstract: Background: As colorectal cancer (CRC) patients with peritoneal metastases (PM) have a poor prognosis, new treatment options are currently being investigated for CRC patients. Specific biomarkers in the primary tumor could serve as a prediction tool to estimate the risk of distant metastatic spread. This would help identify patients eligible for early treatment. Aim: To give an overview of previously studied DNA and RNA alterations in the primary tumor correlated to colorectal PM and investigate which gene mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Another study, based on NGS (Next Generation Sequencing) analysis, showed that KRAS mutation occurred in 63.6% of 22 Indonesian patients with mostly advanced CRC [42]. Distinct mutations located in codons 13, 14, 34, 58, 59, and 146 were found as opposed to more commonly reported mutations in codons 12, 13, 61, 146 [42][43][44]. A recent study in China has also reported that KRAS mutation was found in 69.4% of the early lesions [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Another study, based on NGS (Next Generation Sequencing) analysis, showed that KRAS mutation occurred in 63.6% of 22 Indonesian patients with mostly advanced CRC [42]. Distinct mutations located in codons 13, 14, 34, 58, 59, and 146 were found as opposed to more commonly reported mutations in codons 12, 13, 61, 146 [42][43][44]. A recent study in China has also reported that KRAS mutation was found in 69.4% of the early lesions [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to our explorative study, we performed a systematic review to summarize the current knowledge on genetics and genomics in CRC-PM [ 19 ]. An NGS analysis with 409 cancer genes showed several additional genetic mutations, i.e., ARID1A , PKHD1 , UBR5 , PAX5 , TP53 , ASXL1 , and AR , presumably associated with PM [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to identify genomic changes in primary CRC that are associated with development of PMs, which would allow early detection and personal and early patient treatment. Such a study has not been reported yet [ 17 , 19 ], despite the growing attention and possibilities for the genomic analysis of cancer using, for example, next-generation sequencing (NGS) techniques with broad gene panels investigating DNA and RNA alternations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review paper summarized the use of various molecular techniques (e.g., RT-PCR, PCR, and single nucleotide polymorphism (SNP) genotyping assay, NGS, NanoString analysis, Sanger sequencing, MassArray sequencing, quantitative MSP) to investigate changes at the DNA and RNA level that may predict CRC metastasis to the peritoneum. Only BRAF mutations were associated with peritoneal metastases in 10/17 studies [ 353 ].…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%